2021
DOI: 10.3390/e23070839
|View full text |Cite
|
Sign up to set email alerts
|

Increased Entropic Brain Dynamics during DeepDream-Induced Altered Perceptual Phenomenology

Abstract: In recent years, the use of psychedelic drugs to study brain dynamics has flourished due to the unique opportunity they offer to investigate the neural mechanisms of conscious perception. Unfortunately, there are many difficulties to conduct experiments on pharmacologically-induced hallucinations, especially regarding ethical and legal issues. In addition, it is difficult to isolate the neural effects of psychedelic states from other physiological effects elicited by the drug ingestion. Here, we used the DeepD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
(74 reference statements)
1
14
0
Order By: Relevance
“…Crucially, these results seem to corroborate at the behavioral level the findings from Greco et al 37 , in which they observed a general increased entropic brain dynamics due to DeepDream exposure. Therefore, it seems reasonable to interpret these mouse trajectories findings in light of the entropic brain hypothesis 32 , 35 , according to which, during psychedelic experiences, the brain is supposed to operate at a criticality state, where it has access to a larger repertoire of physical states and therefore has a more chaotic dynamics.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Crucially, these results seem to corroborate at the behavioral level the findings from Greco et al 37 , in which they observed a general increased entropic brain dynamics due to DeepDream exposure. Therefore, it seems reasonable to interpret these mouse trajectories findings in light of the entropic brain hypothesis 32 , 35 , according to which, during psychedelic experiences, the brain is supposed to operate at a criticality state, where it has access to a larger repertoire of physical states and therefore has a more chaotic dynamics.…”
Section: Discussionsupporting
confidence: 90%
“…DeepDream is a computational procedure that alters images relying on a pre-trained deep convolutional neural network (CNN), a process also referred to as “algorithmic pareidolia” 37 . The algorithm starts by passing an input image with width ( ) and height ( ) through the CNN up to a selected layer .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent developments in VR technology suggest that it could be possible to induce mystical experiences 52,53 and imitate parts of the phenomenology of the psychedelic state 54 . Also, some recent studies have suggested that using psychedelic phenomenology in VR can lead to similar cognitive 55 and neural 56 effects as seen under psychedelic substances. Thus, these recent works raise the intriguing possibility that perhaps the implementation of such phenomenology in VR could be used to confer similar therapeutic benefits to psychedelicaugmented therapy.…”
Section: Introductionmentioning
confidence: 99%